Small dams need consideration in riverscape conservation assessments. Issue 4 (7th March 2017) - Mantel, Sukhmani Kaur; Rivers‐Moore, Nick; Ramulifho, Pfananani
Abstract: Small, off‐channel dams are generally ignored in impact assessments owing to limited information and spatial resolution issues. Previous research on South African rivers showed correlative links between high density of small dams and associated reductions in low flows, poorer water quality, and impoverished aquatic macroinvertebrate communities that were dominated by opportunistic taxa instead of specialist groups. Since small dams are usually associated with catchment transformation (for example, vineyards, stock farming and exotic timber plantations), they are convenient surrogates of the impacts of catchment transformation on river functionality. Here, an index of cumulative small dams for South Africa, Lesotho and Swaziland is presented and evaluated. Fifty‐two per cent of the water management catchments in the study region exceeded the threshold for the cumulative small dams density (SDD) index above which river functionality is compromised. This estimate of potentially affected catchments is considered to be conservative for reasons discussed. The index results are compared with a recent systematic biodiversity planning exercise for setting biodiversity targets for freshwater areas of South Africa. Although the systematic planning included in‐stream small dams within 50 m of a river, analysis showed that 36% of all quaternaries that have high SDD score overlap with river reaches classified as 'natural' or 'largely natural'. Disregarding dams outside the 50 m buffer area equates to ignoring the majority of small dams (94%) in South Africa, and it is recommended that aquatic conservation assessments include the SDD index as a cost layer for prioritizing rivers for rehabilitation and conservation.